(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify (Good & lavoie) model in achievement and the acquisition of thinking skills among the second intermediate stage students in mathematics. To achieve the goal of the current study, The study sample consisted of (77) female students in the second stage average in the middle school (Al-Muthanna for Girls) affiliated to the General Directorate of Education of Baghdad / Al-Rusafa Al-Awwala. the study sample was randomly selected to represent section (A) of (39) students as the experimental group which were trained according to a model Good & lavoie, Section (C) of (38) students representing the control group that was taught according to the traditional method. The two groups were rewarded in the variables (the chronological age of the students calculated in months, the intelligence test, the previous mathematical knowledge, the previous achievement of mathematics, and the test of complex thinking skills). consisted of (30) items, including (14) items. Objective (multiple choice) and (16) essay items. The validity and stability coefficient using the alpha- Cronbach equation. while for the complex thinking skills test items it reached (0.74). The experiment was applied to the study sample in the second course of the academic year (2022-2023), and after The end of the experiment The test of complex thinking skills in mathematics were applied to the two research groups, and by using the appropriate statistical means, the results showed that there was a statistically significant effect at the level of significance (0.05) between the two research groups (experimental and control) in the test of complex thinking skills in mathematics and in favor of experimental group. In the light of these results, it was concluded that the Good & Lavoie model has an effect on the acquisition of complex thinking skills, the researcher suggests holding training courses to train male and female teachers on how to use the Good & Lavoie model in teaching mathematics, the most important proposals is to conduct a study similar to the current study in different mathematical topics and other educational stages, as well as knowing the effectiveness of teaching mathematics using the Good & Lavoie model in other dependent variables such as reflective thinking skills, and mathematical communication skills and attitudes towards mathematics.